(untitled) (Kinesiology, 2018)
Factors related to physical behaviour of children are important in understanding the characteristics of their physical activity. Apart from the factors of physical environment, social and demographical factors are also related to physical activity levels. Randomly selected 669 children (9.9±0.8 years; 48.8% boys) from randomly selected Slovenian elementary schools participated in this study. All data were obtained during a single measurement in May 2010. The standardized questionnaire The Quality of Life Survey was used to measure physical activity (PA) levels as well as social and demographic factors which could be associated with it. The results indicated higher PA levels in boys than in girls (704±286 min/week vs. 617±268 min/week; p<.001). The analysis of variance confirmed higher PA levels in girls with parents of a higher socioeconomic status (SES) (p=.0018); in boys, there were no differences in PA levels according SES (p=.580). In both the boys (p=.047) and girls (p=.021) PA levels were higher if their whole family were members of any sport club. However, family structure was not related to PA levels in either boys (p=.648) or girls (p=.132). In boys, the bi-variate regression analysis showed a positive correlation with mother’s educational level (r=.090), with the number of children in the family (r=.150), with the child’s attitude that active commute to school is attractive (r=.108) and that child’s peers actively commute to school (r=.129), whereas a negative correlation was obtained with fear the child would become a victim of violence or harassment on the way to school (r=-.097). In girls, bi-variate regression analysis showed a positive correlation with mother’s educational level (r=.094), with the child’s attitude that active commute to school is attractive (r=.092) and that child’s peers actively commute to school (r=.221), whereas a negative correlation was established with fear the child would become a victim of violence or harassment on the way to school (r=-.061) or at recreational and sporting facilities (r=-.046). According to low correlations in bi-variate analysis, we conclude that other factors, such as, for example, physical environment, might be strongly related to physical activity levels in children and need to be taken into account when preparing interventions for physical activity enhancement. Key words: children, adolescents, socioeconomic status, active commute